Artificial lung ventilation in patients with morbid obesity during laparoscopic operations in the Trendelenburg position (literature review) - M. N. Gurin; V. M. Golovach; I. V. Berlev; V. A. Glushchenko; S. A. Rosengard (Вестник анестезиологии и реаниматологии)
The literature review is devoted to the peculiarities of artificial lung ventilation (ALV) in patients with morbid obesity during laparoscopic oncosurgical interventions in the Trendelenburg position. At present, there are no consensus recommendations on the choice of the optimal ALV mode during anesthesia in this area of oncosurgery. When analyzing data obtained from other types of operations, there was no impression that there were significant advantages of any ALV modes, both with volume and pressure control. However, high values of positive end-expiratory pressure (PEEP) have the most evidence of benefit in this category of patients, and the inversion of the duration of the respiratory cycle phases without creating a high PEEP can help reduce the risk of lung damage when all other ALV techniques do not allow for adequate oxygenation.